Innovative Approach to Minimize Balancing Weight in Railway Wheel Sets - Kushawaha, Jeetender Singh (Journal of Railway Transportation and Technology, 2024)
This study elaborates the re-iterative, trial & error procedure adapted to reduce the excessive consumption of balancing weights in the railway wheel sets during wheel set assembling. The process involved MATLAB programming for dynamic balancing equations and CAD simulations to arrive at the solution. On the completion of the study and implementation of findings, the reduction in the consumption of balancing weight by 95.9% has been realized.